2013
DOI: 10.1007/s00022-013-0198-7
|View full text |Cite
|
Sign up to set email alerts
|

Cycles in projective spaces

Abstract: We prove that every possible k-cycle can be embedded into P G(n, q), for all n ≥ 3 and q a power of a prime.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In [21] Lazebnik, Mellinger, and Vega demonstrate that it is possible to embed a 2k-cycle of every possible size into the Levi graph of any finite affine or projective plane. This was further extended by Aceves, Heywood, Klahr, and Vega [1] who showed that one can embed a 2k-cycle of every possible size into the Levi graph of the projective space P G(d, q). Moreover, in a different paper Lazebnik, Mellinger, and Vega [22] motivated the study of counting 2k-cycles in the Levi graph with the following two questions.…”
Section: Introductionmentioning
confidence: 87%
“…In [21] Lazebnik, Mellinger, and Vega demonstrate that it is possible to embed a 2k-cycle of every possible size into the Levi graph of any finite affine or projective plane. This was further extended by Aceves, Heywood, Klahr, and Vega [1] who showed that one can embed a 2k-cycle of every possible size into the Levi graph of the projective space P G(d, q). Moreover, in a different paper Lazebnik, Mellinger, and Vega [22] motivated the study of counting 2k-cycles in the Levi graph with the following two questions.…”
Section: Introductionmentioning
confidence: 87%